2019
DOI: 10.1007/s11071-019-05081-8
|View full text |Cite
|
Sign up to set email alerts
|

Limit cycles at oversteer vehicle

Abstract: Handling and stability properties of automobiles are most often studied from a practical point of view by applying a reduced set of equations, where the forward velocity is kept constant. At studying the full set of equations of a basic nonlinear two-wheel vehicle model, a supercritical Hopf bifurcation is found for an oversteer vehicle. All state variables of the vehicle are involved at small amplitude limit cycles in the vicinity of the Hopf bifurcation point with the steering angle (drive torque) as bifurca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This approximation suggests the reduction of the dynamics onto the critical manifold, like it is often assumed (e.g. [27]). Interestingly, this approximation is not sufficient to study the inversion phenomenon of the tippedisk.…”
Section: Discussionmentioning
confidence: 86%
“…This approximation suggests the reduction of the dynamics onto the critical manifold, like it is often assumed (e.g. [27]). Interestingly, this approximation is not sufficient to study the inversion phenomenon of the tippedisk.…”
Section: Discussionmentioning
confidence: 86%
“…Depending on the specific use-case and the accuracy needed, there exist many variations of this model [34,39]: The simplest vehicle models assume rigid wheels with no tire deformation [19,26], but a wide range of tire models are also available in the literature to describe the tire-road interaction [33]. The arising side forces and self-aligning moments are commonly considered as different linear and nonlinear functions of the side slip angles [21,45], but more involved tire models can also be applied [5]. Additional modeling aspects include the consideration of geometrical nonlinearities [10,30,45], the drive type of the vehicle [30], the inertia of the steering system [49] and the caster length of the steered wheel [48].…”
Section: Introductionmentioning
confidence: 99%
“…The arising side forces and self-aligning moments are commonly considered as different linear and nonlinear functions of the side slip angles [21,45], but more involved tire models can also be applied [5]. Additional modeling aspects include the consideration of geometrical nonlinearities [10,30,45], the drive type of the vehicle [30], the inertia of the steering system [49] and the caster length of the steered wheel [48]. When selecting the appropriate vehicle model, a balance needs to be found between model complexity and fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the linear stability of equilibria, Varszegi et al 20 found that the vehicle may lose stability in oscillatory and non-oscillatory ways corresponding to Hopf and pitchfork bifurcations, respectively. Steindl et al 21 found that small amplitude limit cycles close to the Hopf bifurcation point emerge with the steering angle (drive torque) as bifurcation parameter, followed by large amplitude relaxation cycles.…”
Section: Introductionmentioning
confidence: 99%